Cyber security capability maturity model based on Maqasid A Shari’ah (MS-C2M2) - Abdul Aziz, Normaziah; Saidin, Aznan Zuhid; Wahiddin, Mohamed Ridza; Ibrahim, Jamaludin; Ahmad Dahlan, Abdul Rahman; Ahmad H.Osman, Rahmah; M. Ridza, Nadwiyah (2020)
Motivation and objective of the research are due to the ever increasing cybercrime and how important for each organization to be assisted in addressing it. A comprehensive approach to address protection and prevention of cyber attacks is very necessary. But it all has to begin with knowing what is the status of the organization, first. Such status is known as Cyber Security Maturity (CSM) index or Cyber Security Readiness. This research works on CSM index. There are various CSM model of measuring the index. Our value add is incorporating Maqasid al Shari’ah in our CSM model.